Synthesis of Novel Ester-Based 5-Fluorouracil Derivatives - Ayik Rosita Puspaningtyas; Ika Oktavianawati (Jurnal Kimia Sains dan Aplikasi, 2024)
Fluorouracil (5-Fu, 1) is an antimetabolite cancer drug and the first-line drug of anticancer administration by WHO that has been widely used worldwide for more than 50 years. The development of 5-fluorouracil is an effort to obtain higher activity, decrease side effects, and create a specific target receptor compared to 5-fluorouracil. In this research, a series of novel 5-Fluorouracil (5-Fu) derivatives has been synthesized based on a benzoylation reaction (Schotten-Baumann reaction) of N1-hydroxylated 5-Fu called compound 2, 5-fluoro-1-(hydroxymethyl)-uracil. The benzoyl chloride substituents used in this research, including 3-chlorobenzoyl (4a), 2-chlorobenzoyl (4b), 3-nitrobenzoyl (4c), 4-methoxy benzoyl (4d), 4-trifluoromethylbenzoyl (4e), 3,4-dichlorobenzoyl (4f), and 4-nitrobenzoyl (4g) chloride become (4a-4f)-5Fu. This research meticulously examined the conditions (time and reaction temperature) at the second step of the synthesis reaction (esterification), ensuring the reliability of the results. The best synthesis conditions for 4a, 4b, 4c, 4d, and 4g compounds were found to be reflux at 40°C for 6 hours, whereas 4e and 4f compounds reactions were performed in an ice bath for 11 and 17 hours, respectively. All product syntheses, 4a-4g compound, were purified using column chromatography and eluted using eluent hexane: acetone (6:4), and the yields of 4a-4g compounds were around 61-79%. The pure compounds were characterized using FTIR and 1HNMR spectrometer, further validating the research. Based on these findings, it can be concluded that all 5-Fu derivatives can be synthesized using the Schotten-Baumann reaction method.